Anotaciones al margen de la teoría y la práctica de una arqueología marginal y marginada, realizada sobre espacios geográficos invisibles. Estudio de caso: Antioquia (Colombia) (2008)
ABSTRACT: Based on a detailed analysis of reports and publications, the interpretative and methodological determinants of archaeological record from Colombia are explored. This is done in a region where many traces of an antique and dynamic settlement process remain ignored and invisible. The proposal intends to demonstrate how the writing of history has imposed mechanically repeated arguments and practices, which in the end have masked and lost crucial evidences and a broader object of study.